Culvert baffle design to improve fish passage for small‐bodied fishes: A rapid evidence synthesis - Paul A. Franklin; Cindy F. Baker (Conservation Science and Practice, 2025)
Abstract Culverts are one of the most prevalent barriers to the upstream movement of small‐bodied fishes. Installation of baffles, structures designed to modify flows, within culverts is one of the main solutions for overcoming the impact of high water velocities on fish movements. The objective of this rapid evidence synthesis was to review and summarize the evidence on the effectiveness of different culvert baffle designs for improving the abundance and diversity of small‐bodied fish successfully migrating upstream through culverts. The overall weight of evidence indicates that the addition of baffles generally increases overall passage success compared with control treatments with no baffles. However, effectiveness cannot be determined based on simple passage efficiency metrics alone. Multiple lines of evidence are emerging to indicate that turbulence within baffle arrays can significantly delay upstream movements. A consensus is emerging that baffles that minimize the generation of large recirculation zones while maximizing the area of low‐velocity boundary layers (i.e., spoiler, vertical, and longitudinal baffles) are most suitable for improving the upstream passage of small‐bodied fishes. However, there remain significant knowledge gaps and an urgent need for comparative assessments of baffle performance alongside ongoing innovation to refine and optimize baffle designs for small‐bodied species.